The diagnosis and endovascular therapy of renal artery aneurysm: A 32-patient case report. Issue 47 (November 2017) - Tang, Shiying; Niu, Guochen; Fang, Dong; Yan, Ziguang; Zhang, Bihui; Li, Xuesong; Yang, Min; Zhou, Liqun
Abstract: Rationale: Renal aneurysm is a rare disease with the atypical symptoms and mostly diagnosed by imaging modalities. Endovascular therapy is a one of treatment methods. Patient concerns: A retrospective analysis of 32 patients with renal artery aneurysm, from June 2010 to May 2016 in our hospital, was made in our study. All of them underwent therapy, and the effects and perioperative characteristics of it were analyzed. Diagnosis: 32 patients were taken contrast-enhanced CT and diuretic renal dynamic imaging to evaluate the state of illness. Interventions: The preoperative blood creatinine, perioperative hemoglobin and relief of hypertension were performed. Outcomes: The preoperative blood creatinine was slightly increasing, while the perioperative hemoglobin was slightly decreasing. The relieving hypertension was performed in 9 of patients. Lessons: Endovascular therapy is a mature and feasible treatment method. There is little effect on hemoglobin and renal function in postoperation, while it can also decrease the blood pressure.